2023
DOI: 10.3390/jof9020140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Arbuscular Mycorrhizal Fungi on the Growth and Root Cell Ultrastructure of Eucalyptus grandis under Cadmium Stress

Abstract: Eucalyptus grandis (E. grandis) has been reported to form a symbiosis with arbuscular mycorrhizal fungi (AMF), which plays an important role in improving plant tolerance of heavy metal. However, the mechanism of how AMF intercept and transport cadmium (Cd) at the subcellular level in E. grandis still remains to be researched. In this study, a pot experiment was conducted to investigate the growth performance of E. grandis under Cd stress and Cd absorption resistance of AMF and explored the Cd localization in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…This result was similar to the result of You's study, which showed that the host plants are most dependent on mycorrhizal fungi under higher concentrations of heavy metal stress [35]. Previous studies have demonstrated that AMF are present in various metal-contaminated sites and can develop tolerance to excessive amounts of various trace elements [37][38][39][40]. Similar results were found in this study as the AMF species showed a good Mo tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…This result was similar to the result of You's study, which showed that the host plants are most dependent on mycorrhizal fungi under higher concentrations of heavy metal stress [35]. Previous studies have demonstrated that AMF are present in various metal-contaminated sites and can develop tolerance to excessive amounts of various trace elements [37][38][39][40]. Similar results were found in this study as the AMF species showed a good Mo tolerance.…”
Section: Discussionsupporting
confidence: 91%
“…This means that when plant shoots are infected with arbuscular mycorrhizal fungi, the plant's ability to absorb and accumulate heavy metals such as Cd, Pb, Cu, Mn, Fe, Ni, Cr, and As in its shoots decreases. Several recent researchers have also reported that AMF have the ability to inhibit the translocation of heavy metals to the shoots [28,[34][35].…”
Section: Discussionmentioning
confidence: 98%
“…In the research by Kuang et al, the scholars aimed to explore the impacts of diverse cadmium (Cd) levels on the translocation ratio and mycorrhizal efficiency in E. Grandis with AMF colonization. The findings revealed intriguing discoveries that illuminated the interaction between cadmium (Cd), AMF, and plant physiology [17]. The scientists administered varying quantities of Cd to E. Grandis, with a range of sizes from 50 μm to 500 μm.…”
Section: Effect Of Soil Pollutants On Amf Colonizationmentioning
confidence: 99%